Comparison of Using Android-based Lux Meter and Split Flux Method in Natural Lighting Material in Building Physics Course - Nuzulul Alifin Nur (Universitas Negeri Yogyakarta, 2023)
Background: The use of learning media is very influential in the learning process. In natural lighting calculation material, students usually use the Split Flux method, but the calculation is long because students have to provide a solar arc in the form of a printout on mica. So in this study, students will be divided into several groups to calculate natural lighting using an android-based lux meter.Methods: The approach used in this research is a quantitative approach, with an empiricist paradigm, and with a survey method. The survey was conducted on students who had taken the Building Physics course. The survey was conducted using an instrument. The instrument is an open and closed questionnaire.Results: The survey results show that (1) 73% of respondents chose the answer 51% to 75%, meaning that 73% of students understand the split flux method and 28% of respondents chose 75% to 100%, meaning that 28% of students understand the split flux method; (2) 78% stated that it was easier to use an android-based lux meter to measure natural lighting; (3) 79% stated that it was faster to use an android-based lux meter to measure natural lighting.Conclusion: By using an android-based lux meter, students can install it on their respective handphone, besides students are facilitated in measuring natural or artificial lighting and are not paid, besides that the process is faster and more flexible by using the help of android-based lux meter media in Building Physics courses, students become more interested in learning natural lighting measurements because they can easily take lighting measurements in a room.